2000
DOI: 10.1128/jvi.74.22.10341-10348.2000
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Subgenomic RNA Directed by a Satellite RNA Associated with Bamboo Mosaic Potexvirus: Analyses of Potexvirus Subgenomic RNA Promoter

Abstract: Satellite RNA of bamboo mosaic potexvirus (satBaMV), a single-stranded positive-sense RNA encoding a nonstructural protein of 20 kDa (P20), depends on bamboo mosaic potexvirus (BaMV) for replication and encapsidation. A full-length cDNA clone of satBaMV was used to examine the sequences required for the synthesis of potexvirus subgenomic RNAs (sgRNAs). Subgenomic promoter-like sequences (SGPs), 107 nucleotides (nt) upstream from the capsid protein (CP) gene of BaMV-V, were inserted upstream of the start codon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…2a, c) . Potexviruses have three subgenomic RNAs for expression of TGB and CP (Huisman et al, 1988;Lee et al, 2000). An octanucleotide sequence (AACUAAAC) in the PVX 59 NTR was identified that can base pair with sequences Fig.…”
Section: Rna Elements Regulating Potexvirus Replicationmentioning
confidence: 99%
“…2a, c) . Potexviruses have three subgenomic RNAs for expression of TGB and CP (Huisman et al, 1988;Lee et al, 2000). An octanucleotide sequence (AACUAAAC) in the PVX 59 NTR was identified that can base pair with sequences Fig.…”
Section: Rna Elements Regulating Potexvirus Replicationmentioning
confidence: 99%
“…P20 is an RNA-binding protein that can be replaced with other proteins such as chloramphenicol acetyltransferase (CAT). Thus, satBaMV has been developed as a useful plant expression vector (Lee et al, 2000;Lin et al, 1996). The helper virus BaMV, a member of the Potexvirus genus, contains a single-stranded positive-sense RNA genome with 5 conserved ORFs Yang et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since CP is required for cell-to-cell movement of potexviruses [33,34], we have constructed potexvirus-based viral vectors by replacing the CP open reading frame (ORF) with that of the TP in order to prevent the undesired spread of the viral vectors. It has been previously shown that nucleotides (nts) +1 to +15 at the 5′-terminal of BaMV-S strain CP ORF are essential for CP subgenomic RNA promoter activity (SGP) [35]. Thus, a pKB-derived vector, pKB△C His , was generated, containing multiple cloning sites ( Mlu I- Stu I- Not I -Spe I) and 6X His tag to facilitate the purification of TP and nts +1 to 15 at the 5’ terminus of BaMV CP gene, of which initiation codon was mutated.…”
Section: Methodsmentioning
confidence: 99%